2021
DOI: 10.3390/rs13081531
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Urbanization Patterns in Four Rapidly Growing South Asian Cities Using Sentinel-2 Data

Abstract: The rapid and dominant urbanization in Asian cities has fueled concerns regarding the local and global efforts toward urban sustainability. Specifically, South Asian cities have been a topical issue concerning ecological and environmental threats due to their unplanned and haphazard urban development. However, comparative urbanization studies in South Asian cities remain uncommon. Therefore, in this study, we sought to comparatively examine the land use and land cover (LULC) dynamics and to detect the urbaniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 98 publications
(153 reference statements)
1
15
0
Order By: Relevance
“…Hassan et al [11] conducted a comparative study to examine the changes in the thermal environment in seven South Asian megacities from 2000 to 2019 using yearly average LST from MODIS data with a 1-km spatial resolution. A comparative study was conducted to detect the urbanization patterns of four rapidly developing lowland South Asian cities, including Karachi, in 2019 [29]. Despite these efforts, multitemporal satellite remote sensing data have been insufficiently employed, and our knowledge on the long-term evolution of SUHI and concurrent LULC changes in Karachi is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al [11] conducted a comparative study to examine the changes in the thermal environment in seven South Asian megacities from 2000 to 2019 using yearly average LST from MODIS data with a 1-km spatial resolution. A comparative study was conducted to detect the urbanization patterns of four rapidly developing lowland South Asian cities, including Karachi, in 2019 [29]. Despite these efforts, multitemporal satellite remote sensing data have been insufficiently employed, and our knowledge on the long-term evolution of SUHI and concurrent LULC changes in Karachi is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Seto and Fragkias [4] emphasised that the concentric rings capture development processes from the urban centre of various urban-rural areas. Ranagalage et al [62] applied a gradient analysis using concentric rings around the urban core centre to capture the spatial distribution dynamics of land use and cover from the city centre to the rural areas. This is emphasised also in this research, in which the analysis of the concentric rings showed the urban patterns for each buffer during each period, including the outskirts.…”
Section: Discussionmentioning
confidence: 99%
“…13 Details of other demographic characteristics, including anthropometric measurements, physical activity, smoking, alcohol consumption, and diet, are described elsewhere. 38,42 Briefly, BMI was calculated as weight (kg)/height (meter) 2 , and waist-to-hip ratio (WHR) was calculated as the ratio of waist circumference to hip circumference. Blood pressure (BP) was measured twice after a 5-min seated rest period with the participant's feet flat on the floor.…”
Section: Study Subjectsmentioning
confidence: 99%
“… 1 The region of South Asia (consisting of people from India, Pakistan, Bangladesh, Nepal, Bhutan, and Sri Lanka) is the epicenter of the growing epidemic of T2D due to rapid urbanization, immense population growth, and aging. 2 , 3 Studies performed on immigrant Indians outside India have shown that T2D and coronary artery disease incidence is three to six times higher in immigrant Asian Indians (AIs) than Euro-Caucasians. The onset of T2D is roughly a decade earlier [even at a lower body mass index (BMI)] in AIs than in Europeans.…”
Section: Introductionmentioning
confidence: 99%